2008
DOI: 10.1097/jes.0b013e3181877d71
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Variability in Human Walking and Running is Speed-Dependent

Abstract: The variability of gait in human walking and running is not random but shows self-similarity that is dependent on the speed of locomotion. The strength of the long-range correlations for each gait pattern follows a U-shaped function that is centered on the respective preferred speed of locomotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 15 publications
5
38
0
Order By: Relevance
“…Runners initially demonstrated high a. Consistent with previous reports of fatigue, the significant linear tread suggests an overall decrease of longrange correlations over the course of the run [17][18][19]. One possible explanation provided for this reduction is an increased need for adjustments occur with fatigue.…”
Section: Reduced a With Prolonged Runningsupporting
confidence: 82%
“…Runners initially demonstrated high a. Consistent with previous reports of fatigue, the significant linear tread suggests an overall decrease of longrange correlations over the course of the run [17][18][19]. One possible explanation provided for this reduction is an increased need for adjustments occur with fatigue.…”
Section: Reduced a With Prolonged Runningsupporting
confidence: 82%
“…The increased variability suggests that the participant has more ability to alter his gait pattern than before training and represents a favorable outcome. 22 Overall, this study strengthens existing evidence that sensory activity patterned according to the task can improve this task as already proposed before. 1,3 However, the importance of the pattern of the sensory stimulation remains to be thoroughly evaluated since whole-body vibration has also been found to improve gait speed to a similar extent (0.06 m s − 1 ) among 17 persons with a chronic SCI participants with similar clinical characteristics.…”
Section: Discussionsupporting
confidence: 73%
“…Subsequent studies using a variety of different techniques have confirmed the presence of long-range correlations and fractal-like scaling in the gait of healthy young adults ͑see below͒, even during slow walking and during running. [80][81][82][83][84][85][86][87] From a neurophysiological control viewpoint, this behavior is of interest because it signifies the presence of longterm, non-trivial "dependence" or "memory" in the locomotor control system. This scale-invariance property has been associated with the survivability of the system in several physical and physiological systems.…”
Section: Beyond the First And Second Moments: Fractal Analysis Of mentioning
confidence: 99%